THE INFLUENCE OF WORK ENVIRONMENT, TRANSFORMATIONAL LEADERSHIP AND ORGANIZATIONAL CULTURE ON JOB SATISFACTION AND IMPLICATIONS FOR EMPLOYEE PERFORMANCE - Budi Rismayadi (Universitas Padjadjaran, 2022)
The purpose of this paper is to determine the effect of the work environment, transformational leadership and organizational culture on job satisfaction and its implications for employee performance. Methodology The population of this research is all 142 hotel employees in Pangandaran and Resort, Indonesia. The number of samples is determined by the Slovin formula, and the Structural Equation Modeling (SEM) sample consideration is 30 employees. A total of 60 questionnaires were returned and sent for analysis. Proportional stratified sampling was used for technique sampling, and the elements of the sample were determined by the chance sampling method. The analytical method used in this research is descriptive statistics and SEM–Partial Least Square program with IBM Statistical Package for the Social Sciences (IBM SPSS) Statistics 22.0 and WarpPLS 3.0. The hypotheses in this study are how the work environment influences employee performance, (2) how transformational leadership affects employee performance, (3) how organizational culture affects job satisfaction and (4) how does the impact on employee performance at Pangandaran Hotels and Resorts show. work environment, transformational leadership and organizational culture have a positive and significant effect on job satisfaction, but only leadership style has a positive and significant effect on job satisfaction. employee performance. Job satisfaction has no significant and positive effect on employee performance and is not a mediating variable. Originality/value – In conclusion, the role of a leader in the hospitality industry, in this case the general manager (gm), is important. Without a high quality General Manager, job satisfaction and organizational culture will not be achieved.